Pumped storage vs. hydrogen fuel for Nepal's excess hydroelectricity - Karki, Roshan Raj; Pokharel, Sapan; Godar Thapa, Saurav; Hunt, Julian David (Kathmandu University Journal of Science Engineering and Technology, 2024)
Nepal's significant hydropower potential is hindered by seasonal variations in electricity generation, resulting in surplus power during the monsoon season and deficits in the winter months. This study addresses the need for efficient energy storage solutions to mitigate reliance on expensive electricity imports. We investigate the economic viability of two storage techniques: pumped hydro energy storage (PHES) and hydrogen storage. By conducting a cost comparison analysis, we assessed the levelized cost of electricity (LCOE) for each method under varying input electricity costs. Our results show that PHES is currently the more cost-effective option, with an LCOE of USD 22.43/MWh in an ideal scenario with free electricity, compared to hydrogen storage's USD 100/MWh. Even with a paid electricity cost of USD 50/MWh, PHES maintains a lower LCOE of USD 77.99/MWh, whereas hydrogen storage's LCOE increases significantly. Future advancements in hydrogen technology could reduce its LCOE to around USD 31.25/MWh, making it competitive for low energy storage needs. Our findings highlight PHES as the most practical solution for Nepal's immediate energy storage needs, while underscoring the potential of hydrogen storage for long-term clean energy integration.